2020
DOI: 10.1039/d0nr04141f
|View full text |Cite
|
Sign up to set email alerts
|

Large-area periodic arrays of gold nanostars derived from HEPES-, DMF-, and ascorbic-acid-driven syntheses

Abstract: A method for the nanofabrication of periodic arrays of gold nanostars yielding a unique morphology of relevance to SERS applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 83 publications
1
35
0
Order By: Relevance
“…The pH sensitivity of organic acids' redox potentials allows for their use in seeded growth syntheses. Arguably the most utilized reducing agent for branching AuNPs, AA has been applied to form gold multipods, 36 stars, 74 urchins, 19 dendrites, 75 and more 26,76,77 and can be examined as a model for organic acid reductants. Work from our group has shown the facile room-temperature non-seeded synthesis of quasispherical gold particles by ascorbic acid as the sole reducing and capping agent.…”
Section: Reducing Agent Choicementioning
confidence: 99%
“…The pH sensitivity of organic acids' redox potentials allows for their use in seeded growth syntheses. Arguably the most utilized reducing agent for branching AuNPs, AA has been applied to form gold multipods, 36 stars, 74 urchins, 19 dendrites, 75 and more 26,76,77 and can be examined as a model for organic acid reductants. Work from our group has shown the facile room-temperature non-seeded synthesis of quasispherical gold particles by ascorbic acid as the sole reducing and capping agent.…”
Section: Reducing Agent Choicementioning
confidence: 99%
“…Alternatively, substrate-immobilized NSs can be obtained from substrates hosting seed arrays. Demille et al recently demonstrated the synthesis of NSs using near-hemispherical Au structures as substrate-bound seeds . These seed structures were prepared from a template with cylindrical holes obtained by nanoimprint lithography, deposition of Au/Sb by sputtering, template lift-off, and thermal reshaping of the resulting disks into quasi-hemispheres with diameters of ca.…”
Section: Introductionmentioning
confidence: 99%
“…These deficiencies stimulate researchers to combine the physical fabrication technique and the chemical seed‐mediated growth for broadening the diversity of substrate‐supported Au NP morphology. [ 42 ] Yet, it is still hard for the substrate‐supported Au seeds to obtain reactants by the traditional growth process under room temperature, or conventional reductants such as ascorbic acid, leading to the failure of their sustained growth into Au NP with controllable morphology. Up to now, it is still of a great challenge to develop an effective route which not only makes the seeds maintain the original arrangement but also allows their controllable growth into more abundant substrate‐supported NPs.…”
Section: Introductionmentioning
confidence: 99%